Hybrid Learning through Lecture Capture: Exploring Perspectives and Overcoming Challenges with Blackboard Encore Technology - Zhao, Xin (International Journal of Emerging Technologies in Learning (iJET), 2023)
The COVID-19 pandemic has resulted in significant disruptions in higher education. Despite UK universities returning to in-person teaching, many international students still face travel restrictions imposed by their home countries, resulting in remote learning for many students at the beginning of the 2022–2023 academic year. To ensure a seamless academic transition for all students, a British university has implemented a hybrid learning model that utilizes lecture capture technology, specifically Blackboard Encore Streaming, to provide face-to-face and remote students with access to the same learning experience. This paper presents the findings from two online focus groups with students (n = 18) and two staff reflections, which aimed to explore the perspectives of teachers and students on the new Encore Streaming feature. The results indicate that both teachers and students value the hybrid approach, with remote students appreciating the flexibility and convenience of this approach more than face-to-face students. However, the study also reveals significant discrepancies in teacher attention and student participation opportunities between remote and face-to-face students, attributed to pedagogical and technological barriers. The study highlights the crucial role of teachers in orchestrating the hybrid classroom to ensure equal learning opportunities for all students and identifies areas where teachers require support, such as training, staff time, and technology support.